2020
DOI: 10.20543/mkkp.v36i2.6140
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh ukuran partikel arang dari limbah tutup botol plastik terhadap kualitas briket

Abstract: The amount of plastic waste increases with the increase in plastic use, especially in the food industry. Plastic waste is waste that is very difficult to decompose and takes a long time to spoil. Plastic bottle caps are a type of polypropylene (PP) plastic which is recommended to be used only once. The research objective was to determine the effect of particle size on the briquette characteristics of plastic bottles based on the proximate analysis. The proximate analysis carried out was moisture content, ash c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…High-energy briquettes have a calorific value of 26,5-33,8 MJ/kg, which is significantly comparable to the maximum value reported for high-energy coal of 27 MJ/kg, while the compressive strength is 0,7 MPa [6]. Research conducted [7] by utilizing plastic bottle caps from home industrial health drink lids (infused water) and tapioca flour shows that at 40 mesh particle size, best properties i.e. moisture content 0,5 ± 0,05%, ash content 2 ± 0,25%, volatile content 15 ± 0,51%, combined carbon content 82,5 ± 0,32%, and 9.982,779 ± 240,017 calorific value in cal/gr.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…High-energy briquettes have a calorific value of 26,5-33,8 MJ/kg, which is significantly comparable to the maximum value reported for high-energy coal of 27 MJ/kg, while the compressive strength is 0,7 MPa [6]. Research conducted [7] by utilizing plastic bottle caps from home industrial health drink lids (infused water) and tapioca flour shows that at 40 mesh particle size, best properties i.e. moisture content 0,5 ± 0,05%, ash content 2 ± 0,25%, volatile content 15 ± 0,51%, combined carbon content 82,5 ± 0,32%, and 9.982,779 ± 240,017 calorific value in cal/gr.…”
Section: Introductionmentioning
confidence: 68%
“…Based on the close-up analysis result of 9.982,779 ± 240,017 cal/gr. From this, it can be concluded that the particle size of 40 mesh can improve the briquette quality compared to 100 mesh [12]. The next research is to determine the emission of carbon monoxide (CO) and the combustion rate of briquettes mixed with rice husk and teak sawdust and their effect on the grain size of the briquettes.…”
Section: Introductionmentioning
confidence: 99%
“…First, weigh 1 gram of the bio-briquette sample, then place it in the cup. The cup filled with bio-briquette samples was put into the furnace with a temperature of 750 ± 20 ℃ for 7 minutes, after which the sample was cooled in a desiccator and weighed; the volatile matter content is calculated by the following equation (Ningsih et al, 2020).…”
Section: Volatile Contentmentioning
confidence: 99%
“…Fixed carbon content is a parameter of bio-briquette quality. The fixed carbon content indicates the combustible carbon content after the expulsion of volatile materials (Ningsih et al, 2020). The level of fixed carbon will significantly affect the ignition of bio-briquettes.…”
Section: Carbon Fixed Contentmentioning
confidence: 99%
“…Diverifikasi produk pemanfaatan plastik untuk bahan campuran briket merupakan salah satu alternatif pengoptimalan sampah plastik atau limbah lainnya. Briket sampah botol plastik dan bahan sintesis diuji nilai kalor, kadar air, kadar abu, kadar zat menguap dan kadar karbon terikat untuk mengetahui pengaruh bahan plastik dan bahan sintesis terhadap kualitas briket (Ningsih et al, 2020) Berdasarkan Tabel 2. Pengmatan uji nilai kalor briket campuran sampah botol plastik dan bahan sintesis dengan perekat lumpur Sidoarjo menggunakan perbandingan komposisi bahan 50 gr : 30 gr : 20 gr, serta perbandingan komposisi perekat kanji 100 gr : 8 gr menghasilkan nilai kalor sebesar 19,75 MJ/kg atau apabila dikonversi satuan kalori sebesar 4717 cal/gr.…”
Section: Hasil Dan Pembahasanunclassified